2011
DOI: 10.1016/j.jmii.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tigecycline monotherapy compared with vancomycin-aztreonam in the treatment of complicated skin and skin structure infections in patients from India and Taiwan

Abstract: Tigecycline monotherapy is a safe and effective therapy for cSSSIs in geographically distinct populations in Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…After reading the remaining 170 full-text papers, 121 studies were excluded for the following reasons: studies with an irrelevant study design (n = 46), non-RCTs (n = 16), lacking outcomes (n = 8), duplication of published articles (n = 6), and review and meta-analysis (n = 46). Finally, 48 studies [27–74] were included in the meta-analysis. The study selection process was performed in accordance with the PRISMA guidelines and Figure 1 showed the PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…After reading the remaining 170 full-text papers, 121 studies were excluded for the following reasons: studies with an irrelevant study design (n = 46), non-RCTs (n = 16), lacking outcomes (n = 8), duplication of published articles (n = 6), and review and meta-analysis (n = 46). Finally, 48 studies [27–74] were included in the meta-analysis. The study selection process was performed in accordance with the PRISMA guidelines and Figure 1 showed the PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…When a subsequent trial was done with double the dose of tigecycline, tigecycline was similar in efficacy to imipenem for the same disease [4]. Subsequent trials in skin and soft tissue infections (SSTIs) [5][6][7][8], community-acquired pneumonia [9][10][11][12], and intraabdominal infections [13][14][15][16] showed equivalent clinical efficacy for tigecycline and several bactericidal comparators (Supplementary Table 1). A metaanalysis suggested worse outcomes with tigecycline compared to competitors [17].…”
Section: Overall Findingsmentioning
confidence: 99%
“…33 Furthermore, serious adverse events (19/86 patients) were comparable between the 2 groups; even though 4 fatalities occurred in the Indian cohort, 3 in the tigecycline group, these were considered probably not or definitely not related to the study drugs. 33…”
Section: Clinical Efficacy and Safety Of Tigecyclinementioning
confidence: 84%
“…32 Retrospective analysis of data from 2 international, randomized, double blind studies assessing the safety and efficacy of tigecycline monotherapy in Indian (n = 86) and Taiwanese patients (n = 41) hospitalized with cSSSIs revealed comparable cure rates at the test-of-cure-assessment between tigecycline and vancomycin-aztreonam in the clinically evaluable populations in India (83.3% vs. 75.8%) and the clinical modified intent-to-treat populations (78.6% vs. 66.7%). 33 Nausea and vomiting occurred significantly more frequently with tigecycline in comparison to vancomycin-aztreonam; however, the authors concluded that these adverse events were mild to moderate and controlled with appropriate therapy. 33 Furthermore, serious adverse events (19/86 patients) were comparable between the 2 groups; even though 4 fatalities occurred in the Indian cohort, 3 in the tigecycline group, these were considered probably not or definitely not related to the study drugs.…”
Section: Clinical Efficacy and Safety Of Tigecyclinementioning
confidence: 97%
See 1 more Smart Citation